Synthesis, Crystal Structure, Spectroscopic Characterization, DFT Calculations and Cytotoxicity Assays of a New Cu(II) Complex with an Acylhydrazone Ligand Derived from Thiophene - Rodríguez, María Rosa (2021)
Anew Cu(II) complex is synthetized by the reaction of copper nitrate and aN-acylhydrazone ligand obtained from the condensation of o-vanillin and 2-thiophecarbohydrazide (H2L). The solidstate structure of [Cu(HL)(H2O)](NO3) H2O, or CuHL for simplicity, was determined by X-ray diffraction. In the cationic complex, the copper center is in a nearly squared planar environment with the nitrate interacting as a counterion. CuHL was characterized by spectroscopic techniques, including solid-state FTIR, Raman, electron paramagnetic resonance (EPR) and diffuse reflectance and solution UV-Vis electronic spectroscopy. Calculations based on the density functional theory (DFT) assisted the interpretation and assignment of the spectroscopic data. The complex does not show relevant antioxidant activity evaluated by the radical cation of 2,20-azinobis(3-ethylbenzothiazoline- 6-sulfonic acid) diammonium salt (ABTS) method, being even less active than the free ligand as a radical quencher. Cytotoxicity assays of CuHL against three human tumor cell lines, namely MG-63, A549 and HT-29, revealed an important enhancement of the effectiveness as compared with both the ligand and the free metal ion. Moreover, its cytotoxic effect was remarkably stronger than that of the reference metallodrug cisplatin in all cancer cell lines tested, a promissory result in the search for new metallodrugs of essential transition metals.